THE ART EXHIBITIONS IN LIMA AT THE EARLY TWENTIETH CENTURY (1919-1924), IN THE ART CRITIC OF CARLOS SOLARI SÁNCHEZ CONCHA PUBLISHED IN EL COMERCIO DAILY FROM LIMA - Robalino Sánchez, Karla (2010)
This research aims for rescuing and acknowledging a part of the artistic development of the early twentieth century (1919-1924) from the Lima local environment that shows the modern art influence in the Peruvian art construction. Carlos Solari was a Peruvian art critic who worked in El Comercio newspaper, he commented on the art exhibitions carried out among 1919-1924. During these years, most authors used pseudonyms for writing. Solari became known as Don Quijote, also published in other print media as Mundial, although our research is limited to El Comercio daily. It has been considered to mention three painting exhibitions of the 14 painters that Solari referred in his art criticism.